2013
DOI: 10.2355/isijinternational.53.356
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mode of Rolling on Recrystallization Kinetics and Microstructure Evolution in Interstitial Free High Strength Steel Sheet

Abstract: The recrystallization kinetics and microstructure evolution after unidirectional and multi-step cross rolling of interstitial free high strength steel has been investigated systematically. Microhardness, electron backscattered diffraction and X-ray diffraction was used to characterize the recrystallization kinetics, microstructure and texture evolution during annealing. The obtained experimental data on recrystallization was evaluated in terms of Johnson-Mehl-Avrami-Kolmogorov (JMAK) kinetic model. The Avrami … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The effect of deformation mode on recrystallization behaviour of cross-rolled metal was earlier reported by Michalak and Hibbard [21]. UD rolling of pure iron leads to faster recrystallization kinetics hence a smaller recrystallized grain size than cross rolling for the same amount of deformation whereas BD rolling produces a lower dislocation density in the samples compared to UD rolling [7,29] thus lowering the driving force for primary recrystallization and resulting in a lower amount of nucleation sites causing a larger recrystallized grain size readily after 2 h of annealing. Table 3 Mean grain size and preferential orientation information of the as-received and treated samples.…”
Section: Microstructure Evolutionmentioning
confidence: 54%
“…The effect of deformation mode on recrystallization behaviour of cross-rolled metal was earlier reported by Michalak and Hibbard [21]. UD rolling of pure iron leads to faster recrystallization kinetics hence a smaller recrystallized grain size than cross rolling for the same amount of deformation whereas BD rolling produces a lower dislocation density in the samples compared to UD rolling [7,29] thus lowering the driving force for primary recrystallization and resulting in a lower amount of nucleation sites causing a larger recrystallized grain size readily after 2 h of annealing. Table 3 Mean grain size and preferential orientation information of the as-received and treated samples.…”
Section: Microstructure Evolutionmentioning
confidence: 54%
“…They have explained the slow mechanism of initial recrystallization, which attributed to the occurrence of solute atoms in an iron lattice. Moreover, other researchers have reported the variation of 'n' values for high strength IF steel between 1.4 at 675°C and 1.03 at 800°C for unidirectional rolled samples, while 'n' varies between 0.83 at 675°C and 2.6 at 800°C for cross rolled samples [36]. The constant 'k' value decreases with, reflecting the temperature dependence for nucleation and growth rates [3].…”
Section: Recrystallization Kinetics Through Mechanical Softeningmentioning
confidence: 89%
“…The lower activation energy at the initial of recovery is owing to high stored energy developed through high dislocation density at the deformation. The activation energy for Ti-Nb stabilized IF steel increases to 173-312 kJ mol −1 with the effect of excess solute Ti and Nb at the iron lattice or fine carbides and nitrides are accomplished of restraining the recovery process [4,36]. Similarly, Alvarez et al reported that the activation energies of Cr-Mo pre-strained steel are 288.3 and 266.6 kJ mol −1 for 2.6 and 7 pct deformation, respectively [37].…”
Section: Recovery Kinetics Through Magnetic Softeningmentioning
confidence: 96%
See 2 more Smart Citations